2020
DOI: 10.1158/1538-7445.sabcs19-ot3-17-03
|View full text |Cite
|
Sign up to set email alerts
|

Abstract OT3-17-03: Impact of the Oncotype DX breast cancer assay on treatment decisions in a UK population of patients with oestrogen receptor positive early breast cancer with 1-3 lymph nodes positive who are candidates for chemotherapy, but for whom the benefits are uncertain - Interim results

Abstract: Introduction: The addition of adjuvant chemotherapy to hormonal therapy is recommended for patients with lymph node-positive (LN+ve), estrogen receptor positive (ER+), HER2-ve early breast cancer, despite the fact that many women will remain disease-free even if they do not receive chemotherapy. Therefore, a number of patients with LN+ EBC may be unnecessarily exposed to the toxicities of chemotherapy with no treatment benefit. In the UK, the Oncotype DX® Recurrence Score (RS) is recommended by NICE for routin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“… 25 However, in Mattar et al’s study, where patient enrollment was completed almost 1 year after the TAILORx results were released in June 2018, chemotherapy recommendations were reduced from 60%-80% for patients with RS 11-25. 26 Furthermore, the overall reduction in chemotherapy recommendation of 67% in our study was comparable to the magnitude of reduction of 2 recent studies, 66%-74%, 26 , 27 which is higher than several earlier trials. 23-25 , 28-30 This is suggestive that although the TAILORx study consisted of node-negative patients, the cutpoints and results from this study probably influenced physician treatment recommendations among node-positive patients as well.…”
Section: Discussionsupporting
confidence: 82%
“… 25 However, in Mattar et al’s study, where patient enrollment was completed almost 1 year after the TAILORx results were released in June 2018, chemotherapy recommendations were reduced from 60%-80% for patients with RS 11-25. 26 Furthermore, the overall reduction in chemotherapy recommendation of 67% in our study was comparable to the magnitude of reduction of 2 recent studies, 66%-74%, 26 , 27 which is higher than several earlier trials. 23-25 , 28-30 This is suggestive that although the TAILORx study consisted of node-negative patients, the cutpoints and results from this study probably influenced physician treatment recommendations among node-positive patients as well.…”
Section: Discussionsupporting
confidence: 82%
“…Interim results of a UK based trial show that the decision to administer adjuvant chemotherapy changed in 74% of patients, sparing them from chemotherapy. 20 A US-based study found that RS was an independent predictor of chemotherapy recommendation in 1-3 node positive patients. 21 Similar to other studies, we found that the majority of nodepositive patients have a low-risk genomic signature as assessed by the Oncotype Dx test.…”
Section: Discussionmentioning
confidence: 99%
“…Few published studies have examined the role of Oncotype Dx testing in the node positive setting. Interim results of a UK based trial show that the decision to administer adjuvant chemotherapy changed in 74% of patients, sparing them from chemotherapy 20 . A US‐based study found that RS was an independent predictor of chemotherapy recommendation in 1–3 node positive patients 21 …”
Section: Discussionmentioning
confidence: 99%
“…Consideration should also be given to the increasing the use of genomic testing such as OncotypeDx, to identify patients who are most likely to benefit from chemotherapy, especially in borderline cases, such as patients with 1-3 lymph nodes positive. Interim results from the OncotypeDx node positive trial were presented at the San Antonio Breast Cancer Symposium in 2019, and demonstrated that 74% of ER positive, HER2 negative early breast cancer patients with 1-3 nodes lymph nodes positive avoided chemotherapy following OncotypeDx testing [42]. It is also important to bear in mind, that unlike in haematological malignancies, immunosuppression from chemotherapy for breast cancer is usually transient and may be managed using colony stimulating factors, and therefore the likelihood of disease progression or recurrence needs to be balanced against the risks from COVID-19 [43].…”
Section: Chemotherapymentioning
confidence: 99%